KEBEBASAN EKONOMI DI INDONESIA - Dwi Wulandari (Universitas Negeri Malang, 2014)
The Indonesian economy continues to be considered “mostly unfree” due to the lack of progress in other critical areas of economic freedom. Indonesia has lagged in promoting the effective rule of law. The judicial system remains vulnerable to political interference, and property rights are not strongly protected. Despite some progress, lingering corruption continues to undermine enforcement of the rule of law and hampers the realization of Indonesia’s full growth potential. Over the 20-year history of the Index, Indonesia has advanced its economic freedom score by modest overall score. This modest overall score increase has been relatively broad-based, facilitated by improvements in six of the 10 economic freedoms including trade freedom, freedom from corruption, and fiscal freedom, each of which gained 10 points or more. Keywords: Economic freedom, Freedom from corruption, trade freedom, fiscal freedom, monetary freedom, business freedom